Bosenovae with quadratically-coupled scalars in quantum sensing experiments - Jason Arakawa; Muhammad H. Zaheer; Joshua Eby; Volodymyr Takhistov; Marianna S. Safronova (Journal of High Energy Physics)
Abstract Ultralight dark matter (ULDM) particles of mass m ϕ ≲ 1 eV can form boson stars in DM halos. Collapse of boson stars leads to explosive bosenova emission of copious relativistic ULDM particles. In this work, we analyze the sensitivity of terrestrial and space-based experiments to detect such relativistic scalar ULDM particles interacting through quadratic couplings with Standard Model constituents, including electrons, photons, and gluons. We highlight key differences with searches for linear ULDM couplings. Screening of ULDM with quadratic couplings near the surface of the Earth can significantly impact observations in terrestrial experiments, motivating future space-based experiments. We demonstrate excellent ULDM discovery prospects, especially for quantum sensors, which can probe quadratic couplings orders below existing constraints by detecting bosenova events in the ULDM mass range 10−23 eV ≲ m ϕ ≲ 10−5 eV. We also report updated constraints on quadratic couplings of ULDM in case it comprises cold DM.